The Origin of Individual Differences in the Course and Severity of Diseases - Sergey N. Rumyantsev (The Scientific World Journal)
Any disease manifests itself individually either by a bright or restricted spectrum of clinical signs and resultant clinical courses that range from asymptomatic to deadly, from acute to chronic, etc. Until recently, the origin of this kind of biodiversity was poorly investigated and understood, but advances in immunology — especially in identifying constitutional (genetic) mechanisms of immunity — have contributed to our understanding of the origin of individual diversity in diseases. Any disease destroys only focal areas in the affected organisms, and the amounts, sizes, and distribution of such focal lesions vary from patient to patient. In a population predilected to a relevant pathogenic agent, individuals can be conveniently divided into three categories: totally resistant organisms that contain no susceptible structures and are not affected; mildly susceptible organisms in which a few foci appear and in which the disease runs a benign course; organisms in which the number of constitutionally susceptible structures is high and the disease develops in a severe form. The diversity is formed by the mating of genetically different parents that determines the differences in susceptibility of genetically various parts of the descendant organism.